2007
DOI: 10.1111/j.1600-0463.2007.apm_610.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor‐1α expression in experimental cirrhosis: correlation with vascular endothelial growth factor expression and angiogenesis

Abstract: Angiogenesis progresses together with fibrogenesis during chronic liver injury. Hypoxia-inducible factor-1alpha (HIF-1alpha), a master regulator of homeostasis, plays a pivotal role in hypoxia-induced angiogenesis through its regulation of vascular endothelial growth factor (VEGF). The association between hypoxia, angiogenesis and VEGF expression has been demonstrated in experimental cirrhosis. However, expression of HIF-1alpha has yet to be reported. The aim of this study was to investigate the significance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
3
24
3
Order By: Relevance
“…They also evaluated the HIF-1 α levels 2hrs post- TAE as compared to our study where the post-TAE biopsies were taken at 10 min. In another recent study, Bozova et al (10) showed that in an experimental liver fibrogenesis model in Wistar rats, HIF-1 α expression gradually increased as the severity of cirrhosis increased and correlated strongly with the VEGF expression and angiogenesis. We are unaware of any published studies which have evaluated HIF-1 α expression within the same tumor before and after TAE / TACE.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also evaluated the HIF-1 α levels 2hrs post- TAE as compared to our study where the post-TAE biopsies were taken at 10 min. In another recent study, Bozova et al (10) showed that in an experimental liver fibrogenesis model in Wistar rats, HIF-1 α expression gradually increased as the severity of cirrhosis increased and correlated strongly with the VEGF expression and angiogenesis. We are unaware of any published studies which have evaluated HIF-1 α expression within the same tumor before and after TAE / TACE.…”
Section: Discussionmentioning
confidence: 96%
“…In 1992, Semenza et al (8) discovered that Hypoxia inducible Factor-1 α (HIF-1 α) was a control factor regulating the subsequent release of multiple angiogenic factors (Figure 1) (9), including Vascular Endothelial Growth Factor (VEGF), basic fibroblast growth factor (bFGF) and insulin like growth factor (IGF). During TAE, stasis to forward blood flow creates hypoxic conditions and may promote tumor angiogenesis (6, 10) by inducing expression of HIF-1 α (11). …”
Section: Introductionmentioning
confidence: 99%
“…134 In fact, blood vessel density and VEGF expression correlate directly with Child-Pugh score and the proliferative index, size and grade of HCC tumours. [135][136][137][138][139][140] A number of chemokines and their receptors are upregulated in the diseased liver and peripheral blood in the progression of liver fibrosis to cirrhosis and in the pathogenesis of malignant HCC. These molecules regulate inflammation, fibroproliferation, angiogenesis, carcinogenesis, metastasis, and anti-tumour immunity.…”
Section: Activatedmentioning
confidence: 99%
“…This discrepancy might be derived from differences in HCV‐related materials and/or the cell lines used. In the present study, it is worth noting that NS5A, another potentially oncogenic protein of HCV, 10,11 did not induce HIF‐1α upregulation under hypoxia, suggesting that HCV core protein contributes more to hepatocarcinogenesis under hypoxia via angiogenesis, a fundamental biological event in the microenvironment of cirrhotic liver 5,6 …”
Section: Discussionmentioning
confidence: 60%
“…In cirrhotic livers, blood supply is impaired as a consequence of fibrosis, which induces a hypoxic microenvironment in the liver 5 . Indeed, a previous study demonstrates that the expression level of hypoxia‐inducible factor‐1α (HIF‐1α), a nuclear transcription factor, gradually increases with the degree of fibrosis 6 . Under normoxic conditions, HIF‐1α is proline hydroxylated by HIF hydroxylase, resulting in degradation via the ubiquitin‐proteasomal pathway, which involves von Hippel‐Lindau (VHL) protein.…”
Section: Introductionmentioning
confidence: 99%